JIHAD PEREMPUAN DALAM PERSPEKTIF HADIS (STUDI TEMATIK MUJAHID PEREMPUAN DI ZAMAN RASULULLAH SAW) - Muhammad Guntur Amar Rasyid; Husnel Anwar; Fadhilah Is (SHAHIH (Jurnal Ilmu Kewahyuan), 2025)
Studies on jihad in Islam have tended to be dominated by a masculine perspective that positions men as the main actors of the struggle, while the role of women is often marginalized or understood narrowly. In fact, the hadiths of the Prophet Muhammad clearly record the active involvement of women in various forms of jihad during the time of the Prophet, both in the spiritual, social, humanitarian, and supporting dimensions of physical jihad. This study aims to examine the concept of women's jihad from the perspective of hadith through a thematic approach (mauḍū‘ī), by exploring hadiths that contain the role of female mujahideen and analyzing their meaning, form, and relevance in the context of contemporary Islam. This study uses a qualitative method with a type of library research, descriptive-analytical in nature, with primary data sources in the form of hadiths of the Prophet in the main hadith books (kutub al- tis‘ah) and secondary sources in the form of hadith commentary books and classical and contemporary scientific literature. The results of this study indicate that women's jihad in the hadith is not limited to physical warfare, but encompasses spiritual jihad through acts of worship such as the Hajj and Umrah; socio-humanitarian jihad through troop care, logistical support, and strengthening the morale of the community; and moral and intellectual jihad in upholding the values of faith and humanity. Hadiths on the role of women, such as those of Umm ‘Ammārah, Umm ‘Aṭiyyah, Umm Sulaym, and Asmā’ bint Abū Bakr, emphasize that the Prophet Muhammad provided proportional and dignified participation for women according to their capacities and circumstances. This study concludes that women's jihad is an integral part of Islamic teachings oriented toward devotion, welfare, and justice, and has strong relevance in strengthening moderate, inclusive, and gender-just Islamic discourse amidst the challenges of modern society.